Geomagnetic multipoles, 1965.0 - Winch, D. E. (1966)
Following the recent appearance of spherical harmonic coefficients for the potential of the geomagnetic field for epoch 1965.0, the strengths and axes for a dipole, quadrupole and octupole have been computed from first, second and third order spherical harmonic coefficients respectively. An interesting relation existing between the parameters of the dipole, quadrupole and geomagnetic eccentric dipole is also indicated.